Implementation of regional inflation control policy in North Sulawesi Province - Mongi, Henk A. L.; Mokat, Jetty E. H.; Mamonto, Fitri H. (Technium Social Sciences Journal, 2025)
This research aims to describe analyze and interpret the duties of the Regional Inflation Control Team (TPID) and the determinants of Inflation Control policies in North Sulawesi Province. Data collection techniques used in this research are observation, documentation and interviews. The data were analyzed qualitatively descriptively. used in this research is data analysis with an interactive model. The focus of this research is the implementation of TPID tasks (Regional Inflation Control Team program, how to control inflation, the results achieved) and determinant factors (collaboration, supervision, TPID performance evaluation). The results showed that the implementation of regional inflation control policy in North Sulawesi Province has not yet reached the national inflation target of 2.5% ± 1 set by the Government and Bank Indonesia for 2024 due to the non-optimal implementation of TPID tasks. Whereas this inflation control improves people’s welfare and economic growth. The Provincial TPID program has been well structured in accordance with the National Inflation Control Program which refers to the 4K strategic framework namely price affordability, supply availability, smooth distribution, and effective communication. The suggestion from this research is that TPID collaboration with private parties involved in food supply and distribution is needed to ensure supply and price stability in North Sulawesi. The TPID of North Sulawesi Province needs to organize routine field monitoring activities or Market Sidak to monitor prices and supplies directly and formulate appropriate policies that quickly overcome problems in the field.